Dekolonialisasi Gusjigang sebagai Model Green Entrepreneurship untuk Generasi Z - Akbar, Muhammad Ilham; Amalya, Farizka (Universitas Islam Negeri Raden Intan Lampung, 2026)
Abstract; This study aims to transform the local philosophy of Gusjigang comprising (akhlak, ngaji, and dagang) into a conceptual framework of green entrepreneurship for Generation Z, addressing the research problem of Western theoretical dominance and the lack of integration of local wisdom in sustainability discourse. Using a qualitative library research design with systematic literature review and comparative thematic analysis, the study integrates primary sources such as classical Islamic texts and Javanese manuscripts with secondary sources from global scholarship on green entrepreneurship, decolonial studies, indigenous entrepreneurship, and Islamic ecotheology. The findings reveal strong intersections between Gusjigang values and global indicators including eco-innovation, circular economy, ethical sourcing, green marketing, and zero-waste practices, while highlighting unique contributions of spiritual and moral dimensions absent in Western paradigms. The discussion emphasizes the novelty of positioning Gusjigang as an operational decolonial framework, with practical implications for UMKM policy, curriculum design tailored to Generation Z, and strategies aligned with SDGs. In conclusion, the study contributes to expanding theoretical discourse on green entrepreneurship and decolonial approaches, while acknowledging limitations of literature-only data and recommending future empirical validation. Overall, Gusjigang enriches global sustainability discourse and advances epistemic justice. Keywords: Decolonial studies; Generation Z; Gusjigang; Green Entrepreneurship. Abstrak; Penelitian ini bertujuan mentransformasikan falsafah lokal Gusjigang yang mencakup (akhlak, ngaji, dan dagang) menjadi kerangka konseptual green entrepreneurship bagi Generasi Z, dengan menjawab masalah dominasi teori Barat dan minimnya integrasi kearifan lokal dalam wacana keberlanjutan. Metode yang digunakan adalah penelitian kualitatif berbasis kajian pustaka dengan pendekatan systematic literature review dan analisis tematik komparatif, yang mengintegrasikan sumber primer berupa teks klasik Islam dan manuskrip Jawa dengan sumber sekunder dari literatur global tentang green entrepreneurship, studi dekolonial, kewirausahaan indigenous, dan ekoteologi Islam. Hasil penelitian menunjukkan adanya titik temu antara nilai Gusjigang dengan indikator global seperti eco-innovation, circular economy, ethical sourcing, green marketing, dan praktik zero-waste, serta menyoroti kontribusi unik berupa dimensi spiritual dan moral yang tidak ditemukan dalam paradigma Barat. Diskusi menekankan kebaruan penelitian ini dalam memposisikan Gusjigang sebagai kerangka dekolonial operasional, dengan implikasi praktis bagi kebijakan UMKM, desain kurikulum untuk Generasi Z, dan strategi pencapaian SDGs. Kesimpulannya, penelitian ini memperluas diskursus teoretis tentang green entrepreneurship dan pendekatan dekolonial, sekaligus merekomendasikan validasi empiris di masa depan. Secara keseluruhan, Gusjigang memperkaya wacana keberlanjutan global dan memperkuat keadilan epistemik. Kata Kunci: Dekolonialisasi; Gusjigang; Green Entrepreneurship; Generasi Z.